2014
DOI: 10.1124/jpet.113.209353
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans-Retinoic Acid Improves Cholestasis inα-Naphthylisothiocyanate–Treated Rats andMdr2−/−Mice

Abstract: Chronic cholestasis results in liver injury and eventually liver failure. Although ursodeoxycholic acid (UDCA) showed limited benefits in primary biliary cirrhosis, there is an urgent need to develop alternative therapy for chronic cholestatic disorders. Previous studies from our laboratory demonstrated that alltrans-retinoic acid (atRA) is a potent suppressor of CYP7A1, the rate-limiting enzyme in bile acid synthesis. atRA also repressed the expression of tumor growth factor-b and collagen 1A1 in activated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
6
20
0
Order By: Relevance
“…In accordance with pre-clinical findings in animal models of cholestasis 6,7 , we observed inhibition of bile acid synthesis after ATRA and UDCA combination therapy. Specifically, the median serum level of the bile acid intermediate C4 significantly decreased after 12 weeks (9.8±19 vs. 7.6±11 ng/mL, p=.03), Figure 3B .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with pre-clinical findings in animal models of cholestasis 6,7 , we observed inhibition of bile acid synthesis after ATRA and UDCA combination therapy. Specifically, the median serum level of the bile acid intermediate C4 significantly decreased after 12 weeks (9.8±19 vs. 7.6±11 ng/mL, p=.03), Figure 3B .…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, the most beneficial effects in the BDL injury model were found with the combination of ATRA and UDCA. Similar, albeit less dramatic, findings were observed in the other two animal models 7 .…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…This repression of bile acids synthesis enzyme by ATRA was potentiated by UDCA co-treatment [159] , suggesting that the combination therapy may be a superior to monotherapy. In line, recent studies in bile duct-ligated rats and Mdr2 (Abcb4) -/-mice demonstrated that ATRA has complemented UDCA effects in diminishing biliary fibrosis, bile duct proliferation and hepatic inflammation [157,160] . Based on these beneficial effects, the combination therapy of ATRA and UDCA is currently tested in an open label clinical trial in PSC patients (trial number NCT01456468).…”
Section: Bile Acids Receptors and Other (Nuclear Hormone) Receptorsmentioning
confidence: 60%
“…ATRA treatment repressed CYP7A1 promotor activity [39], which was potentiated by UDCA co-treatment [40]. In line, recent studies in bile duct-ligated rats and Mdr2 knockout mice demonstrated that the combination therapy with UDCA-reduced biliary fibrosis, bile duct proliferation and hepatic inflammation [38,41]. Based on these beneficial effects, the combination therapy of ATRA and UDCA is currently tested in an open label clinical trial in PSC patients (trial number NCT01456468).…”
Section: Fxr (And Other Future Therapies) In Treatment Of Cholestaticmentioning
confidence: 96%